Molecular phylogenetic and morphological evidence reveal a rare limacoid snail genus, Khmerquantula gen. nov. (Eupulmonata: Dyakiidae) from Cambodia. Issue 8 (17th November 2021) - Pholyotha, Arthit; Sutcharit, Chirasak; Jirapatrasilp, Parin; Ngor, Peng Bun; Oba, Yuichi; Panha, Somsak
Abstract : An enigmatic land snail species restricted to the karst ecosystem in southern Cambodia and formerly placed in the family Ariophantidae is now reclassified into the family Dyakiidae. Its current systematic position is based on morpho-anatomical characters combined with a molecular phylogeny based on two partial mitochondrial markers (COI and 16S rDNA) and a nuclear gene fragment (28S rDNA). Our results indicate that Khmerquantula gen. nov. is a member of the Dyakiidae with very strong support from both morphological and molecular phylogenetic analyses. The diagnostic characters of this new genus and new species, Khmerquantula leipo are a dextral shell with a well-polished surface, animal with only three dorsal lobes, and reproductive organ without penial verge and amatorial organ papilla. This finding adds a new taxon to current biodiversity and illustrates the growing knowledge of the endemic malacofauna in Cambodia. http://zoobank.org/urn:lsid:zoobank.org:pub:5E5201B1-5BE6-452F-8D1A-B292DBA4AC25 http://zoobank.org/urn:lsid:zoobank.org:act:0D0414A4-FDA5-4E59-BAFE-1E1B68F37E36 http://zoobank.org/urn:lsid:zoobank.org:act:E08633F4-F5E1-4D99-8C70-252DF349C39A